The Role Of Uzbek Language Skills In Enhancing Youth Potential - Bobojonov Sharipboy Xudoshukirovich (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
This article addresses issues such as the reflection of the concept of morality in the Uzbek language and its impact on the spirituality of young people. The article focuses on the moral concepts of youth in our country, such as spirituality, moral education.